Manejo operatorio y no operatorio de las lesiones que afectan el esmalte dental Clínica del Adulto UAN 2017-2022 - Ladino Mejía, Nicol Valeria; Martínez Palomeque, Camila (Universidad Antonio Nariño, 2022)
Over the years, dentistry has evolved in all its areas of knowledge, especially in dental surgery. In the 1950s, research such as that of Buonocore in 1955 on adhesion and acid etching paved the way for the design of less invasive treatments and the invention of biocompatible materials (Carrillo, 2018) The concept of minimally invasive dentistry (IMO) appears thanks to the continuity of these studies, which were based on the theory that disease control is based on the influence on the formation and growth of dental plaque or Biofilm already its kinetic activity in the dissolution of tooth apatites. Consequently, the implementation of demineralization and remineralization processes and/or dental infiltration is triggered as a treatment alternative (Gutiérrez & Planells del Pozo, 2010) The School of Dentistry of the Antonio Nariño University, Armenia, has not been oblivious to these concepts and in this sense, about 4 years ago, included in the requirements to be met every six months the non-operative management of dental caries (education, varnish of fluorine, remineralizing substances, sealants and preventive resins)